2014
DOI: 10.1016/j.medici.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Direct cost of patients with type 2 diabetes mellitus healthcare and its complications in Lithuania

Abstract: The largest part of direct costs in diabetes mellitus healthcare composes hospital inpatient care and covered drugs expenditures. In our study we observed that the presence of microvascular, macrovascular chronic complication increased the direct cost per patient, compared with patients without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…A correlation between the number of complications and the increase of average annual cost per patient was observed, accounting for up to 1588.98 EUR. [30] The results from our study are similar, demonstrating that diabetes is a costly disease when complications develop. In Bulgaria, the costs due to complications are the leading ones, especially when patients should be hospitalized.…”
Section: Sensitivity Analysissupporting
confidence: 76%
See 1 more Smart Citation
“…A correlation between the number of complications and the increase of average annual cost per patient was observed, accounting for up to 1588.98 EUR. [30] The results from our study are similar, demonstrating that diabetes is a costly disease when complications develop. In Bulgaria, the costs due to complications are the leading ones, especially when patients should be hospitalized.…”
Section: Sensitivity Analysissupporting
confidence: 76%
“…[30] The cost included pharmacotherapy and diabetes supplies. The majority of patients were diagnosed with at least one diabetes-related chronic complication.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…The high prevalence of type 2 diabetes mellitus in developed countries substantially increases costs. A study conducted in Lithuania reported that the average cost for a regular patient in 2011 was €156.14, while the average cost for a diabetic patient was €448.34; the costs of medication and medical care weighing on this difference …”
Section: Introductionmentioning
confidence: 99%
“…The American Diabetes Association (ADA) calculated that people with diabetes have healthcare expenditure 2.3 times higher than that for the same population without diabetes . While the care for people with diabetes who experience macro‐ and microvascular complications is particularly costly to the healthcare system; metabolic complications may explain ~11% of the extra costs of the disease . In the Netherlands, the total economic burden of diabetes was calculated to be €6.8 bn in 2016 .…”
Section: Introductionmentioning
confidence: 99%